Collaborative Apps and trust building: OTT and engagement of public in the production of journalistically relevant information (Intercom - Brazilian Journal of Communication Sciences, 2023)
The emergence of experiences of production and circulation of news content generated by nonjournalists is a growing phenomenon, particularly in the last two decades, which causes changes in the media ecosystem, requires the discussion of ethical issues and about trust and credibility, and imposes a set of challenges to traditional journalism. In Brazil, a significant experience in this sense is Onde Tem Tiroteio, created in 2016 as a Facebook fanpage and later transformed into an app. Analyzed here under the methodological prism of virtual ethnography, OTT is constituted as an initiative that, from a process of collaborative production, checking of information, and close relationships between facts and those who report them, acquires journalistic relevance, on the one hand, and demands the deepening of discussions about ethics, credibility, and trust, on the other. At the same time, the profusion of projects such as OTT alerts to the indispensability of traditional journalism to adopt a self-critical look in order to reestablish bonds of trust with society.
Keywords: Journalism; Non-journalists; Participation; OTT; Journalistic trust